PENERAPAN MODEL TEAMS-GAMES-TOURNAMENT (TGT) SEBAGAI UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS MATERI POKOK KEGIATAN EKONOMI KELAS VII. A SEMESTER GANJIL DI SMP NEGERI 1 CERMEE - Eva Yunita; Ahmad Hafas Rasyidi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
Learning activities were lower in social studies / Economics low impact on student learning outcomes. One of the factors that affect the learning model applied to teachers less arouse students' learning activities. The purpose of this research is to improve the activity and student learning outcomes through the application of Teams-Games-Tournament (TGT) in social studies / Economics VII.A semester class at SMP Negeri 1 Cermee. The object of research is VII.A graders by 22 people. The design of this study is modeled by using the scheme Hopkins Tagart 4 phases: planning, action / action, observation and reflection. To obtain the data in this study using observation, interview and test. Data analysis in this study used a qualitative descriptive analysis. On the implementation of the first cycle, followed by 22 students. I cycle daily tests showed mastery learning students very well, reaching 81,82% of the 22 students, then the second cycle followed by all students VII.A class is 22 students and the implementation of daily test results obtained mastery learning has reached 90,91% the same with the results achieved in the implementation of the first cycle, but the implementation of this second cycle level of activity and students' understanding of the material is better than the execution in cycle I.The observations also showed increased activity of the students are pretty good it can be seen from the observation of the activities of the students who performed in the first cycle is equal to 79.54% with Active criteria. And the implementation of the second cycle observations showed satisfactory results, reaching 87.88%.Of all the explanation above, it can be known that the application of learning through the use of multimedia on social studies activities and student learning outcomes can be improved VII.A class because it is consistent with the objectives that you want to accomplish research, thus achieved the second cycle expressed classical completeness .